A new deepwater goby of the genus Discordipinna Hoese & Fourmanoir, 1978 (Teleostei: Gobiidae) from Kumejima of the Ryukyus, Japan - Chen, I-Shiung; Suzuki, Toshiyuki; Shao, Kwang-Tsao (Zootaxa, 2012)
A new goby species of Discordipinna was collected by trawling from the deep waters off Kumejima, the Ryukyu Islands, Japan. The new species, Discordipinna filamentosa, can be well distinguished from the only other described species, D. griessingeri Hoese & Fourmanoir, 1978, by the following unique combination of features: (1) fins: first dorsal fin rays VI; pectoral fin rays 16; and first dorsal fin with the longest, filamentous first ray in male extending far beyond caudal fin base when adpressed; (2) squamation: longitudinal scale rows 26; transverse scale rows 8 and predorsal naked; (3) dorsal pterygiophore formulae 3/122101/9; (4) head lateral-line system: a longitudinal pattern of infraorbital papillae and both anterior oculoscapular canal and preopercular canal present, lacking posterior oculoscapular canal; and (5) its distinctive coloration. An artificial key to species of Discordipinna is also provided.